2015
DOI: 10.1038/srep14084
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diffusion length distribution on polycrystalline silicon wafers via photoluminescence methods

Abstract: Characterization of the diffusion length of solar cells in space has been widely studied using various methods, but few studies have focused on a fast, simple way to obtain the quantified diffusion length distribution on a silicon wafer. In this work, we present two different facile methods of doing this by fitting photoluminescence images taken in two different wavelength ranges or from different sides. These methods, which are based on measuring the ratio of two photoluminescence images, yield absolute value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…L p was measured by the diffusion method described in [19], as well as by the method [20], including the measurement of the photocurrent depending on the absorption depth α -i at a constant intensity F in the region of the intrinsic absorption spectrum. Both methods give almost identical results.…”
Section: Resultsmentioning
confidence: 99%
“…L p was measured by the diffusion method described in [19], as well as by the method [20], including the measurement of the photocurrent depending on the absorption depth α -i at a constant intensity F in the region of the intrinsic absorption spectrum. Both methods give almost identical results.…”
Section: Resultsmentioning
confidence: 99%
“…22 Subsequent work showed that features incorporated into silicon solar cells to boost performance simultaneously increased light emission-a generalisation of Kirchhoff's law linking absorption and emission-with 1% 'wall-plug' efficiency demonstrated. 23 This soon led to the use of charge-coupled arrays to record high-resolution images of light emission over entire wafers, cells 15,16,24 and even modules, 25 techniques now almost universally used in research and manufacturing for diagnostics and characterisation. Extending measurements to fielded modules would greatly enhance benefits, particularly during commissioning, maintenance and troubleshooting.…”
mentioning
confidence: 99%